The SkinBase Project: Providing 3D Virtual Access to Indigenous Skin Clothing Collections from the Circumpolar Area - Schmidt, Anne (Études Inuit Studies, 2016)
In 2014, the National Museum of Denmark (NMD), in conjunction with the Greenland National Museum and Archives (Nunatta Katersugaasivia Allagaateqarfialu [NKA]), as well as the Museum of Cultural History, Oslo, launched the website Skin Clothing Online. The site presents the NMD’s total collection of 2,170 historic skin clothing items, dating from circa 1830 to 1950, from the circumpolar area. The clothing can be studied in minute detail due to high-resolution photos; 100 complete suits were photographed from all sides. Furthermore, 107 items of clothing were measured by means of 3D technology, which can be used to draw precise two-dimensional patterns. The documentation is made accessible to the public through a website, in compliance with creative commons licenses: CC-BY-SA for the photos and CC-BY-SA-NC for the patterns. The website uses content from the database SkinBase. Since 2017 parts of the NKA’s collection of archeological skin clothing from Qilakitsoq (circa 1475 AD), as well as historical garments and contemporary fashions, have also been made accessible, in keeping with the same copyright rules for photos. The NKA staff entered the items into the database without difficulty using a Virtual Private Connection (VPN). The Danish and Greenlandic national museums encourage international partners to contribute items to the website. The aim is to create a collaborative open forum for information and research with easy access for everybody to unique, fragile pieces of circumpolar cultural heritage. With clothing from Arctic peoples and clothing used on expeditions to Antarctica, the Polar Museum in Cambridge will be the next museum to contribute to the website.